2022
DOI: 10.52711/0974-360x.2022.00765
|View full text |Cite
|
Sign up to set email alerts
|

Molecular study on Efflux pumps of Klebsiella pneumonia Isolated from patients with Cystitis

Abstract: Background: Klebsiella pneumoniae can be defined as one of the clinically relevant pathogens that is a common cause of community-acquired and hospital-acquired urinary tract infections (UTI). Objective: The current study was conducted to investigate most common members of 5 classes of efflux pumps among K. Pneumonia isolates. Methodology: K. Pneumonia isolates was diagnosed on EMB and confirmed by tyrB gene. Antibiotic susceptibility test has been done based on the CLSI-2019. Efflux pumps genes were examined v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…This reduction in gene expression was attributed to the use of ceftriaxone (0.3). In addition, the findings of our most recent investigation were consistent with those of another study [11] in which the administration of ceftriaxone was shown to reduce the value of gene expression to levels below 0.5. In this particular investigation, the gene expression value of the Kleb-AdeB gene was found to be 9.33 times higher than the value obtained from the control group.…”
Section: Effect Of Antibiotic Used On Gene Expressionsupporting
confidence: 90%
“…This reduction in gene expression was attributed to the use of ceftriaxone (0.3). In addition, the findings of our most recent investigation were consistent with those of another study [11] in which the administration of ceftriaxone was shown to reduce the value of gene expression to levels below 0.5. In this particular investigation, the gene expression value of the Kleb-AdeB gene was found to be 9.33 times higher than the value obtained from the control group.…”
Section: Effect Of Antibiotic Used On Gene Expressionsupporting
confidence: 90%